Improving Storage Room Organization Through 5S Practices and Visual Device Design - Letchummy Manoghir; Jamian, Rahim (Progress in Engineering Application and Technology, 2025)
Storage rooms are critical to the smooth functioning of organizations across various industrial sectors, serving as hubs for inventory management, storing raw materials, components, finished goods, or essential supplies. Effective management of storage rooms is particularly vital for universities to ensure seamless operations, optimal resource utilization, and a conducive working environment. However, many storage room face challenges such as clutter, disorganization, and inefficiency. This study explored the potential for implementing 5S practices (Sort, Set in order, Shine, Standardize, and Sustain) within a university storage room setting to address these issues. The final year project committee members’ (JKPSM) storage room at the Universiti Tun Hussein Onn Malaysia (UTHM) Pagoh branch campus was selected as a case study. The research examined the challenges, strategies, and outcomes associated with adopting 5S principles, including the use of visual display board to enhance organization and efficiency. Data were gathered through interviews, observations, and documentation review to assess the effectiveness of the implementation process. The main findings significantly highlighted improvements in workplace orderliness, efficiency, and safety following the 5S implementation. This study provided valuable insights into the benefits of systematic organization and cleanliness in enhancing the functionality of universiti storage rooms.